Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the given equation [tex]\(x^2 - 4x + 4 = 2x\)[/tex], we need to go through a few steps. Here’s a detailed, step-by-step solution:
### Step 1: Rewrite the equation
First, move all terms to one side of the equation to set it equal to zero:
[tex]\[ x^2 - 4x + 4 - 2x = 0 \][/tex]
Combine like terms:
[tex]\[ x^2 - 6x + 4 = 0 \][/tex]
Now, we'll rewrite the quadratic equation by completing the square.
### Completing the Square
To complete the square, we follow these steps:
1. Take the coefficient of [tex]\(x\)[/tex], which is [tex]\(-6\)[/tex], divide it by 2, and square it:
[tex]\[ \left(\frac{-6}{2}\right)^2 = 9 \][/tex]
2. Add and subtract this square term inside the equation:
[tex]\[ x^2 - 6x + 9 - 9 + 4 = 0 \][/tex]
This can be rewritten as:
[tex]\[ (x - 3)^2 - 5 = 0 \][/tex]
So the equation in completed square form is:
[tex]\[ (x - 3)^2 = 5 \][/tex]
### Step 2: Find the solutions to the equation
The equation [tex]\((x - 3)^2 = 5\)[/tex] indicates that the solutions are found by taking the square root of both sides. This gives us:
[tex]\[ x - 3 = \pm\sqrt{5} \][/tex]
Thus, we have two potential solutions:
[tex]\[ x - 3 = \sqrt{5} \][/tex]
or
[tex]\[ x - 3 = -\sqrt{5} \][/tex]
Solving for [tex]\(x\)[/tex] in both cases:
1. For [tex]\(x - 3 = \sqrt{5}\)[/tex]:
[tex]\[ x = 3 + \sqrt{5} \][/tex]
2. For [tex]\(x - 3 = -\sqrt{5}\)[/tex]:
[tex]\[ x = 3 - \sqrt{5} \][/tex]
### Numerical Solutions
Providing the numerical solutions for clarity:
[tex]\[ x \approx 3 + 2.236 = 5.236 \][/tex]
and
[tex]\[ x \approx 3 - 2.236 = 0.764 \][/tex]
So, the solutions to the equation [tex]\(x^2 - 4x + 4 = 2x\)[/tex] are approximately [tex]\(x \approx 5.236\)[/tex] and [tex]\(x \approx 0.764\)[/tex].
### Step 1: Rewrite the equation
First, move all terms to one side of the equation to set it equal to zero:
[tex]\[ x^2 - 4x + 4 - 2x = 0 \][/tex]
Combine like terms:
[tex]\[ x^2 - 6x + 4 = 0 \][/tex]
Now, we'll rewrite the quadratic equation by completing the square.
### Completing the Square
To complete the square, we follow these steps:
1. Take the coefficient of [tex]\(x\)[/tex], which is [tex]\(-6\)[/tex], divide it by 2, and square it:
[tex]\[ \left(\frac{-6}{2}\right)^2 = 9 \][/tex]
2. Add and subtract this square term inside the equation:
[tex]\[ x^2 - 6x + 9 - 9 + 4 = 0 \][/tex]
This can be rewritten as:
[tex]\[ (x - 3)^2 - 5 = 0 \][/tex]
So the equation in completed square form is:
[tex]\[ (x - 3)^2 = 5 \][/tex]
### Step 2: Find the solutions to the equation
The equation [tex]\((x - 3)^2 = 5\)[/tex] indicates that the solutions are found by taking the square root of both sides. This gives us:
[tex]\[ x - 3 = \pm\sqrt{5} \][/tex]
Thus, we have two potential solutions:
[tex]\[ x - 3 = \sqrt{5} \][/tex]
or
[tex]\[ x - 3 = -\sqrt{5} \][/tex]
Solving for [tex]\(x\)[/tex] in both cases:
1. For [tex]\(x - 3 = \sqrt{5}\)[/tex]:
[tex]\[ x = 3 + \sqrt{5} \][/tex]
2. For [tex]\(x - 3 = -\sqrt{5}\)[/tex]:
[tex]\[ x = 3 - \sqrt{5} \][/tex]
### Numerical Solutions
Providing the numerical solutions for clarity:
[tex]\[ x \approx 3 + 2.236 = 5.236 \][/tex]
and
[tex]\[ x \approx 3 - 2.236 = 0.764 \][/tex]
So, the solutions to the equation [tex]\(x^2 - 4x + 4 = 2x\)[/tex] are approximately [tex]\(x \approx 5.236\)[/tex] and [tex]\(x \approx 0.764\)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.